Comparison of vision-specific quality of life in patients with monovision and binocular vision after cataract surgery - Praikanarat, Chalermchai (Region 11 Medical Journal, 2020)
Background: After routine cataract surgery, the patients could have good distance vision, otherwise some patients need a wide range of vision and some need spectacle- free for near too. The monovision technique may be the option to meet their expectation. Objective: To compare vision-specific quality of life in patients with monovision and binocular vision after cataract surgery. Method: A prospective study of 80 patients (160 eyes) who underwent bilateral phacoemulsification with a monofocal IOL implantation; 40 with monovision, 40 with binocular vision. The monovision group was corrected a dominant eye as a distance eye with emmetropic target (±0.00 to -0.50 diopter (D)) and a non-dominant eye with myopic target (-1.00±0.50 D) whereas the binocular vision group was corrected both eyes as a distance vision. The outcome were a vision-specific quality of life assessed by a Catquest-9SF 2011 questionnaire preoperative and 6 weeks postoperative of the second eye , uncorrected near and distant binocular visual acuity, near stereoacuity, spectacle independence and postoperative refraction. Results: The postoperative uniocular distance refraction in the monovision (M) group showed the mean spherical equivalent of -0.131D and -0.916 D. In the binocular vision (B) group the mean spherical equivalents were +0.088 D and +0.103 D. The near visual acuity (≤ J5) (M 90.0% vs B 30.0%) and spectacle independence (M 77.5% vs B 7.5%). The distance visual acuity (V.A.≥20/30) (B 100.0% vs M 95.0%) and the near stereoacuity (≤ 100 arc sec) (B 90.0% vs M 87.5%). The quality of life score of the monovision group was better than in the binocular vision group (35.78±0.73 vs 32.97±2.44) (p-value<0.001). Conclusion: Patients in the monovision group provided a higher level of satisfaction than the binocular vision group by means of better vision-specific quality of life. Therefore the monovision technique seems to be a good choice for patients who need a wide range of vision and spectacle independence after cataract surgery.